2009
DOI: 10.1109/tns.2009.2020165
|View full text |Cite
|
Sign up to set email alerts
|

Scintillators With Potential to Supersede Lanthanum Bromide

Abstract: is the most promising. SrI 2 (Eu) emits into the Eu 2+ band, centered at 435 nm, with a decay time of 1.2 µs and a light yield of up to 115,000 photons/MeV. It offers energy resolution better than 3% FWHM at 662 keV, and exhibits excellent light yield proportionality. Transparent ceramics fabrication allows production of Gadolinium-and Terbium-based garnets which are not growable by melt techniques due to phase instabilities. While scintillation light yields of Cerium-doped ceramic garnets are high, light yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(126 citation statements)
references
References 39 publications
4
122
0
Order By: Relevance
“…given by garnet scintillator materials in which the incorporation of Gd onto the Lu 3+ or Y 3+ site, leads to a significant gain of the light yield through an effective energy transfer from the lattice to the activator species via Gd 3+ . 28 …”
Section: Discussionmentioning
confidence: 99%
“…given by garnet scintillator materials in which the incorporation of Gd onto the Lu 3+ or Y 3+ site, leads to a significant gain of the light yield through an effective energy transfer from the lattice to the activator species via Gd 3+ . 28 …”
Section: Discussionmentioning
confidence: 99%
“…Both Gd and Tb offer comparable stopping to Lu, without radioactivity. However, Tb-based garnets exhibit slower decay times than Gd-garnets making them less desirable for gamma spectroscopy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Small crystals (<1 cm 3 ) of SrI 2 (Eu) have been found to provide an energy resolution at 662 keV of 2.5-2.8% [6][7][8][9]. Figure 1 shows a small crystal of SrI 2 (Eu) offering 662 keV energy resolution comparable to that of LaBr 3 (Ce).…”
Section: Resultsmentioning
confidence: 97%
“…Alkaline earth halides are a class of scintillators that appear promising with regards to materials cost, growth, and scintillation yields [1][2][3][4]. We have recently found that single crystal divalent Eu-doped Strontium Iodide yields >100,000 photons/MeV in the Eu 2+ luminescence band (435 nm central wavelength), with a decay time of ~1.2 µs, and excellent light yield proportionality (and hence intrinsic energy resolution) that is superior to that of Ce-doped lanthanum bromide [5][6][7][8][9]. An ongoing coordinated effort between Fisk University, Oak Ridge National Laboratory, Radiation Monitoring Devices, and Lawrence Livermore National Laboratory seeks to improve Strontium Iodide crystal growth and the performance of prototype detectors, with a device goal of 2% resolution at 662 keV and a crystal size of 3" in length by 3" in diameter.…”
Section: Introductionmentioning
confidence: 99%